Application of Molecular Modeling to Development of New Factor Xa Inhibitors. (21st September 2015) - Sulimov, Vladimir B.; Gribkova, Irina V.; Kochugaeva, Maria P.; Katkova, Ekaterina V.; Sulimov, Alexey V.; Kutov, Danil C.; Shikhaliev, Khidmet S.; Medvedeva, Svetlana M.; Krysin, Michael Yu.; Sinauridze, Elena I.; Ataullakhanov, Fazoil I.
Abstract : In consequence of the key role of factor Xa in the clotting cascade and absence of its activity in the processes that do not affect coagulation, this protein is an attractive target for development of new blood coagulation inhibitors. Factor Xa is more effective and convenient target for creation of anticoagulants than thrombin, inhibition of which may cause some side effects. This study is aimed at finding new inhibitors of factor Xa by molecular computer modeling including docking SOL and postdocking optimization DISCORE programs. After validation of molecular modeling methods on well-known factor Xa inhibitors the virtual screening of NCI Diversity and Voronezh State University databases of ready-made low molecular weight species has been carried out. Seventeen compounds selected on the basis of modeling results have been tested experimentally in vitro . It has been found that 12 of them showed activity against factor Xa (IC50 = 1.8–40 μ M). Based on analysis of the results, the new original compound was synthesized and experimentally verified. It shows activity against factor Xa with IC50 value of 0.7 μ M.